Media budaya, pascamodernisme dan ideologi; Suatu kajian lintas disiplin - Budianto, V. Irmayanti (Wacana, Journal of the Humanities of Indonesia, 2002)
Contemporary postmodern culture is characterized by a diversity of cultural forms, the intensive use of high technology, and the multiple identities of its members. The representation of which can be seen in cultural media as in print and electronic media. This study questions the ideological implications of these media and the construction of identities in contemporary society. By analyzing different ads in various Indonesian media with multi-perspective approach, the findings demonstrate how the ideological implications are constructed in imagination, information, technology and figures. In addition, cultural media also involves a network of cultural, social, philosophical and economic aspects in their operations which in turn can cause identity shifts for their users.